2018
DOI: 10.1159/000486042
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte-Rich Thrombus Is Associated with Reduced Number of Maneuvers and Procedure Time in Patients with Acute Ischemic Stroke Undergoing Mechanical Thrombectomy

Abstract: Background: Only few studies have investigated the relationship between the histopathology of retrieved thrombi and clinical outcomes. This study aimed to evaluate thrombus composition and its association with clinical, laboratory, and neurointerventional findings in patients treated by mechanical thrombectomy due to acute large vessel occlusion. Methods: At our institution, 79 patients were treated by mechanical thrombectomy using a stent retriever and/or aspiration catheter between August 2015 and August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(190 citation statements)
references
References 23 publications
7
176
4
3
Order By: Relevance
“…These results are in agreement with a recent study on the structural analysis of acute ischemic stroke that found that red blood cell-rich clots are composed mainly of densely packed red blood cells supported by a thin fibrin network, whilst platelet-rich clots contain dense fibrin structures aligned with vWF and packed with platelets [22]. We demonstrate that platelet-rich clots correlated with a poor revascularization outcome and previous studies have also shown that fibrin/platelets rich clots are more difficult to retrieve that than red blood cell-rich clots [23]. Contracting (activated) platelets have been shown to actively remodel the fibrin network of thrombi leading to an increase in fibrin density and a consequential decrease in clot volume and increase in clot stiffness [24].…”
Section: Subsequent Intracellular Signaling Leads To the Synthesis Ansupporting
confidence: 49%
“…These results are in agreement with a recent study on the structural analysis of acute ischemic stroke that found that red blood cell-rich clots are composed mainly of densely packed red blood cells supported by a thin fibrin network, whilst platelet-rich clots contain dense fibrin structures aligned with vWF and packed with platelets [22]. We demonstrate that platelet-rich clots correlated with a poor revascularization outcome and previous studies have also shown that fibrin/platelets rich clots are more difficult to retrieve that than red blood cell-rich clots [23]. Contracting (activated) platelets have been shown to actively remodel the fibrin network of thrombi leading to an increase in fibrin density and a consequential decrease in clot volume and increase in clot stiffness [24].…”
Section: Subsequent Intracellular Signaling Leads To the Synthesis Ansupporting
confidence: 49%
“…Recent literature also shows inconclusive findings concerning this aspect [24]. There are studies and histological analysis that come to a similar result [25,26], while other investigations indicate the opposite: cardiogenic thrombi seem to have a higher proportion of fibrin compared to other stroke etiologies, associated with worse interventional recanalization rates [27][28][29]. More studies on thrombus etiology and thrombus composition must be performed.…”
Section: Discussionmentioning
confidence: 95%
“…Emerging evidence indicates that RBC-rich stroke thrombi are more easily retrieved via endovascular procedures in comparison to more complex fibrin/platelet-rich thrombi. 14,38 Even though it may seem intuitive that the retriever devices and techniques available today favor more soft thrombi, the mechanisms that render platelet-rich thrombi more resistant to thrombectomy are not completely understood. Weafer et al have recently shown that the degree of clot integration into the thrombectomy device is decreased in fibrin-rich thrombi, making these thrombi more resistant to mechanical removal.…”
Section: Thrombectomymentioning
confidence: 99%